2009
DOI: 10.1088/0022-3727/42/17/175105
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of AlAs oxidation via digital alloy heterostructure compositions

Abstract: A thorough study of wet thermal oxidation in AlAs/AlxGa1−xAs superlattices is presented. The results shown here demonstrate that the final oxidation depth can be finely tuned via the composition and thickness of AlxGa1−xAs into the digital alloy. A complete model of oxidation in these structures is proposed, relying on diffusion through the AlAs layer, its oxidation and an additional effect due to the AlxGa1−xAs intermediate barriers. This barrier contribution is shown to further improve the control of the oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The lateral oxidation rate of the SL was much lower than that of the Al 0.92 Ga 0.08 As layer because of the very thin AlAs layers composing the SL. Indeed, it was reported that the oxidation process from a mesa edge is slowed down significantly in such thin AlAs layers [22,25,26]. Close to the mesa edge (position A) and from the interface between the SL and the oxidized Al-rich layer, it is found that only three SL periods representing $12 nm are oxidized.…”
Section: Vertical Oxidation Of Sl Layermentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral oxidation rate of the SL was much lower than that of the Al 0.92 Ga 0.08 As layer because of the very thin AlAs layers composing the SL. Indeed, it was reported that the oxidation process from a mesa edge is slowed down significantly in such thin AlAs layers [22,25,26]. Close to the mesa edge (position A) and from the interface between the SL and the oxidized Al-rich layer, it is found that only three SL periods representing $12 nm are oxidized.…”
Section: Vertical Oxidation Of Sl Layermentioning
confidence: 99%
“…The intrinsic strain induced by oxidation volume shrinkage was also studied by micro‐photoluminescence . AlAs/Al x Ga 1 − x As superlattice (SL) can also be used instead of uniform AlGaAs layers in order to achieve an easy control of the alloy composition and a precise tuning of the oxidation depth . After oxidation, better mechanical properties were obtained .…”
Section: Introductionmentioning
confidence: 99%
“…depend on the geometrical characteristics of the interface between the (unoxidized) semiconductor and the oxidized areas resulting from the partial lateral oxidation of mesas whose etched sidewalls have been exposed to water. To address the above-mentioned requirement and potentially enhance the device manufacturability, several models have been developed to reproduce the process kinetics [12] [13] [14] [15] [16] [17] [18] [15] [19] [20] [21] [22]. These models are, in essence, all based on the empirical model established by Deal and Grove which describes and quantifies the temporal evolution of the oxidation depth of surface oxidized silicon wafers in terms of the interplay between the diffusive and reactive nature of the process [23].…”
Section: Introductionmentioning
confidence: 99%
“…As the Al-III-V semiconductor oxidation progresses laterally from the sidewalls of etched mesas rather than from the wafer surface, the reported models have primarily been concerned with the extension from one dimension to 2-to-3-dimensions as well as with the analysis of the associated consequences. It has thus been shown that the process kinetics depends on the etched mesa geometry [12] [13] [14] [15] [16] [17], on the thickness of the to-be-oxidized layer [18] [15] [19] [20] and of its (oxidizing) surroundings [21] [22]. In all these models, the process is assumed to be isotropic and, therefore, the shape of the oxide aperture would then readily be inferred from the etched mesa geometry by a homothetic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…3, we have fitted the experimental oxidation depths corresponding to the upper and lower bound of the oxidation front, using the Deal-Grove model. Based on a set of parameters determined in a previous work, 21 we have adjusted the diffusion coefficient D to achieve the best fit between the model and the experimental data. In this way, we have access to the diffusion coefficient.…”
mentioning
confidence: 99%